Firebolt eaudiobook - Woods, Adrienne (Dragonian, 2017)
Dragons. Right. Teenage girls don't believe in fairy tales, and sixteen-year-old Elena Watkins was no different—until the night a fairy tale killed her father. Now Elena's in a new world, and a new school. The cutest guy around may be an evil dragon, a Prince wants Elena's heart, and a long-dead sorcerer may be waking up to kill her. Oh, and the only way Elena's going to graduate is on the back of a dragon of her own. Teenage girls don't believe in fairy tales. Now it's time for Elena to believe—in herself.